HASIL BELAJAR SISWA SEKOLAH DASAR: TINJAUAN ATAS MODEL PEMBELAJARAN, MOTIVASI BELAJAR, GAYA BELAJAR DAN FASILITAS BELAJAR - Didit Darmawan; Laela Nur Afifah (Hijri, 2026)
This literature study aims to analyze the interaction between learning models, learning motivation, learning styles, and learning facilities in determining the learning outcomes of elementary school students. The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that varied and student-centered learning models can arouse intrinsic motivation through experiences of competence, autonomy, and social relatedness. Learning motivation functions as the driving energy that determines the level of effort students expend in engaging with the learning process. Diverse learning styles require teachers to present material through multiple modalities so that each student can access information through the pathway most suitable for them. Adequate learning facilities provide the material infrastructure that supports the optimization of the learning process and enables teachers to implement differentiated instruction. The synergy between these four factors creates a conducive learning ecosystem for achieving optimal learning outcomes. This study contributes theoretically to enriching the ecological perspective on elementary education and practically provides reflective foundations for teachers, principals, and policymakers in optimizing learning processes and facilities.